2017
DOI: 10.1002/cpp.2135
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance in psychological therapy for people with schizophrenia and related psychoses: A systematic review

Abstract: Therapeutic alliance is a key predictor of therapy outcomes. Alliance may be particularly pertinent for people with schizophrenia as this group often have a history of interpersonal trauma and relationship difficulties including difficult relationships with mental health staff. This review aimed to determine (a) the quality of therapeutic alliance between people with schizophrenia and their therapists; (b) whether alliance predicts therapeutic outcomes; and (c) variables associated with alliance. Databases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 83 publications
(255 reference statements)
8
73
2
1
Order By: Relevance
“…An auditory hallucinations simulation study with student nurses demonstrated that the simulation improved understanding of voice hearing, increased students' awareness of its impact on functioning, and led to greater consideration of the communication skills needed to engage with people who hear voices (Orr et al, ). Fostering such important therapist factors has been shown to be associated with better client‐rated therapeutic alliance in psychosis (Shattock, Berry, Degnan, & Edge, ). Research shows that increasing empathy towards members of stigmatized groups can improve attitudes towards the whole group (Batson, Chang, Orr, & Rowland, ).…”
Section: Introductionmentioning
confidence: 99%
“…An auditory hallucinations simulation study with student nurses demonstrated that the simulation improved understanding of voice hearing, increased students' awareness of its impact on functioning, and led to greater consideration of the communication skills needed to engage with people who hear voices (Orr et al, ). Fostering such important therapist factors has been shown to be associated with better client‐rated therapeutic alliance in psychosis (Shattock, Berry, Degnan, & Edge, ). Research shows that increasing empathy towards members of stigmatized groups can improve attitudes towards the whole group (Batson, Chang, Orr, & Rowland, ).…”
Section: Introductionmentioning
confidence: 99%
“…To some degree, our findings expand on their results, as we used therapists' ratings of the therapeutic alliance as a direct measure of social functioning instead of self-ratings. Again, if our exploratory findings can be replicated and positive ER skills are a protecting factor against the negative influence of delusions on the therapeutic relationship, patients' ER abilities might also influence the effectiveness of CBT for psychosis, as a positive therapeutic relationship is closely related to the effectiveness of CBT [28,75,76]. Interestingly, one study indeed found general ToM abilities (including ER) to moderate change in positive symptoms in CBT [77].…”
Section: Discussionmentioning
confidence: 59%
“…One paradigm of a social interaction in real life is the therapeutic alliance defined as affective bond and consensus with regard to goals and treatment tasks [25]. As the therapeutic alliance is highly important for the effectiveness of Cognitive Behavior Therapy (CBT [26][27][28]), it is crucial to assess whether problems in ToM and ER might have a negative effect on it. This question has been investigated in one study reporting associations between ToM problems and patients' ratings on the quality of the therapeutic alliance [29].…”
Section: Introductionmentioning
confidence: 99%
“…To some degree, our findings extent their results, as we used therapists' ratings of the therapeutic alliance as a direct measure of social functioning instead of self-ratings. Again, if our exploratory findings can be replicated and positive ER skills are a protecting factor against the negative influence of delusions on the therapeutic relationship, patients' ER abilities might also influence the effectiveness of CBT for psychosis, as a positive therapeutic relationship is closely related to the effectiveness of CBT (28,63,64).…”
Section: Discussionmentioning
confidence: 71%